Studi Literatur : Pengaruh Asi Eksklusif Dan Berat Badan Lahir Rendah (BBLR) Terhadap Kejadian Stunting Pada Balita - Gita Shakinah Sitepu; Riris Oppusunggu; Sudana Fatahillah Pasaribu (Lembaga Pengembangan Kinerja Dosen, 2023)
Stunting is a chronic nutritional problem that has long-term effects and reflects growth failure in children. According to the 2018 Indonesian Basic Health Research, the prevalence of stunting in toddlers was 30.8%. Factors that are related to the incidence of stunting consist of family factors and child factors. Family factors that can cause stunting include short mothers, caregiver education and economic status, child factors that can cause stunting, namely LBW, late initiation of early breastfeeding, non-exclusive breastfeeding, complementary breast milk foods that are not suitable in quality and quantity, poor micronutrient quality and infectious diseases.The aim of the research was to determine the effect of exclusive breastfeeding and low birth weight on the incidence of stunting in toddlers.This research method is a literature review by identifying 11 articles that have been selected according to the research objectives. Article selection was carried out by determining inclusion and exclusion criteria consisting of duplication, title, abstract and PICOS criteria. The databases used in searching for articles are Google Scholar, NELITI, and PubMed. Indonesian keywords are stunting in toddlers, exclusive breastfeeding, and low birth weight. The English keywords are Exclusive breastfeeding and Low Birth Weight, Stunting in toddlers or a combination of these keywords connected by AND/OR.The research results showed that, based on the search results of 11 scientific articles, 7 articles concluded that there was an influence of exclusive breastfeeding on the incidence of stunting with each p<0.05. Based on the search results of 11 scientific articles, 4 articles concluded that there was an influence of LBW on incidence of stunting with each p<0.05.